(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2014)
Offline signature verification was the first approach to be applied for solving the signature verification problem. It involves the discrimination of genuine and forged signatures on static images. Unlike online systems, offline systems have only the static image containing the signature as an input, without having any knowledge on the signing process. Some difficulties that may arise in offline systems are related to the scanning process (noise on the image) and to the signature acquisition process where different pen tips and widths can produce different shapes. This paper presents a brief study on offline signature verification and recognition using various methods, FAR and FRR is calculated for each method and results are compared.